2014
DOI: 10.1093/carcin/bgu052
|View full text |Cite
|
Sign up to set email alerts
|

TR4 nuclear receptor functions as a tumor suppressor for prostate tumorigenesis via modulation of DNA damage/repair system

Abstract: Testicular nuclear receptor 4 (TR4), a member of the nuclear receptor superfamily, plays important roles in metabolism, fertility and aging. The linkage of TR4 functions in cancer progression, however, remains unclear. Using three different mouse models, we found TR4 could prevent or delay prostate cancer (PCa)/prostatic intraepithelial neoplasia development. Knocking down TR4 in human RWPE1 and mouse mPrE normal prostate cells promoted tumorigenesis under carcinogen challenge, suggesting TR4 may play a suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 33 publications
3
44
2
Order By: Relevance
“…This is in contrast to an early study showing TR4 might suppress PCa initiation (6), suggesting that TR4 might play dual roles with a suppressor role in PCa initiation and a promoter role in PCa S/P cells invasion. Mechanism dissection suggested that TR4 might inhibit PCa initiation via positively regulating DNA damage-repair related gene ATM, thus enhancing DNA repair to prevent tumorigenesis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to an early study showing TR4 might suppress PCa initiation (6), suggesting that TR4 might play dual roles with a suppressor role in PCa initiation and a promoter role in PCa S/P cells invasion. Mechanism dissection suggested that TR4 might inhibit PCa initiation via positively regulating DNA damage-repair related gene ATM, thus enhancing DNA repair to prevent tumorigenesis.…”
Section: Discussioncontrasting
confidence: 99%
“…Results from TR4 knockout (TR4KO) mice studies have shown that TR4 may play key roles to influence embryonic development, stem cell pluripotency and progression of several diseases including metabolic disorders and various tumors (26). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a survey of PCa samples also found that one allele of the TR4 gene is deleted in 9% of PCa patients (SJ Lin, CY Lin, K Izumi, E Yan, X Niu, DR Yang, N Wang, Li G and C Chang, unpublished observations). These results indicate that TR4 is a tumor suppressor gene in the early development of PCa (Lin et al 2014). However, in vitro migration/invasion assays and in vivo mouse studies also found that TR4 promoted migration/invasion of various PCa cells via modulation of CCL2/CCR2 axis, indicating that TR4 can enhance PCa metastasis (XF Ding, DR Yang, SO Lee, YL Chen, LQ Xia, SJ Lin, SC Yu, YJ Niu, GH Li and C Chang, unpublished observations).…”
Section: Cancermentioning
confidence: 66%
“…C/C mice developed PIN and formed PCa tumors at 15 months (Lin et al 2014). Interestingly, a survey of PCa samples also found that one allele of the TR4 gene is deleted in 9% of PCa patients (SJ Lin, CY Lin, K Izumi, E Yan, X Niu, DR Yang, N Wang, Li G and C Chang, unpublished observations).…”
Section: Cancermentioning
confidence: 94%
“…A total of 8 mice were housed in a specific pathogen-free laboratory, airconditioned, with a 12/12 h light/dark cycle. Subcutaneous implantation was performed as previously described (27) where mice were injected subcutaneously with DUSP1-Vector or DUSP1-OE SGC996 cells. A total of 1x10 6 SGC996 stable cells (mixed with Matrigel in a ratio of 1:1) were injected subcutaneously.…”
Section: Rt-qpcrmentioning
confidence: 99%